Role of unfolded protein response in genital malformation/damage of male mice induced by flutamide. (December 2020) - Yu, H; Wen, K; Zhou, X; Zhang, Y; Yan, Z; Fu, H; Zhu, J; Zhu, Y
The unfolded protein response (UPR) is one of a switch of autophagy and apoptosis, and the endoplasmic reticulum stress (ERS) which inducing UPR plays a role in the malformations caused by some genetic and environmental factors. Exposure to flutamide during pregnancy will also cause abnormalities in some male offspring reproductive organs such as cryptorchidism. In this study, after administered the pregnant mouse orally at a dose of 300 mg/kg body weight every day during gestational day (GD)12 to GD18, flutamide can not only caused hypospadias in the male mouse offspring but also damaged the morphology and function of their testis. And the expression of UPR-related genes and proteins, autophagy, apoptosis, and angiogenesis-related genes of the damaged/teratogenic testis and penis in the mice were investigated to determine the role of UPR in this model. It was found that flutamide activated maybe the Atg7-Atg3-Lc3 pathway through the UPR pathway, caused cells excessive autophagy and apoptosis, and inhibited the formation of penile and testicular blood vessels by activating UPR and affecting the messenger RNA level of vascular endothelial growth factor and hypoxia-inducible factor 1.